Transepistemes Safeguarding the Nature of Life, Emerging from A-signifying Ruptures - Milagros Elena Rodríguez (Perspectivas Metodológicas​)
The complex objective of the investigation is to support asignificant ruptures that provoke inclusion in the transepistemes of the nature of life in the investigation, is everything valid in inclusion? Research is rhizomatic, planetary decolonial, complex and transmethodical. In the lines of research: education-transcomplex transepistemologies; transepistemologies of knowledge-knowledge and transcomplex transmethodologies; Planetary decoloniality-complexity in re-linkage. In the propositional moments, asignificant ruptures are immersed whose motto is: Everything that affects the nature of life is exclusive of life itself; because the alteration brings unimaginable consequences that deliver the modifications to the uncontrollable consequences.